Implementasi Kebijakan Penanggulangan Bencana Banjir Di Desa Balinggi Jati Kecamatan Balinggi Kabupaten Parigi Moutong Provinsi Sulawesi Tengah - Susyanti, Ni Putu Ayu; Tawil, Muzakir; Labiro, Richard F. (JPS: Journal of Publicness Studies, 2026)
This study analyzes the implementation of flood disaster management policies in Balinggi Jati Village, Balinggi District, Parigi Moutong Regency, Central Sulawesi Province. Flood events occurring almost every year indicate that the implementation of disaster management policies still reflects a separation among the pre-disaster, emergency response, and post-disaster stages. This research employs a descriptive qualitative approach, with data collected through observation, interviews, and documentation involving the Regional Disaster Management Agency (BPBD) of Parigi Moutong Regency, the Balinggi Jati Village Government, and local communities. The analysis is guided by the policy implementation framework proposed by Knill and Tosun (2020). The findings show that flood disaster management policy is more oriented toward response and post-disaster activities, such as evacuation, aid distribution, and environmental recovery. Meanwhile, pre-disaster mitigation and preparedness have not been systematically developed due to limited budget support and situational inter-agency coordination. These findings highlight the need to strengthen an integrated disaster management policy across all phases, particularly through enhanced pre-disaster planning and institutional capacity at the village level